2022
DOI: 10.1021/acs.langmuir.1c03399
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of a Stable Monolayer of Active Acetylcholinesterase on Planar Gold

Abstract: Enzyme activity is the basis for many biosensors where a catalytic event is used to detect the presence and amount of a biomolecule of interest. To create a practical point-of-care biosensor, these enzymes need to be removed from their native cellular environments and immobilized on an abiological surface to rapidly transduce a biochemical signal into an interpretable readout. This immobilization often leads to loss of activity due to unfolded, aggregated, or improperly oriented enzymes when compared to the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 76 publications
2
14
0
Order By: Relevance
“…The activity remained the same over the course of three weeks (after which the experiment was ended), demonstrating that binding to the AuNP imparted stability on the enzyme. We have previously reported that native aqueous AChE completely loses activity after 6 days of storage at 4 °C but remains stable when adsorbed onto a flat macroscopic Au surface . The data presented in Figure B corroborates the observation that immobilization onto a scaffold of some kind, regardless of its size, imparts stability on the enzyme’s function.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The activity remained the same over the course of three weeks (after which the experiment was ended), demonstrating that binding to the AuNP imparted stability on the enzyme. We have previously reported that native aqueous AChE completely loses activity after 6 days of storage at 4 °C but remains stable when adsorbed onto a flat macroscopic Au surface . The data presented in Figure B corroborates the observation that immobilization onto a scaffold of some kind, regardless of its size, imparts stability on the enzyme’s function.…”
Section: Resultssupporting
confidence: 87%
“…We have previously reported that native aqueous AChE completely loses activity after 6 days of storage at 4 °C but remains stable when adsorbed onto a flat macroscopic Au surface. 31 The data presented in Figure 4B corroborates the observation that immobilization onto a scaffold of some kind, regardless of its size, imparts stability on the enzyme's function. This is significant since it shows that the act of immobilizing proteins onto a platform is not only key to integrating proteins into inorganic materials but is also in fact beneficial to the stability and function of any device using this strategy over time.…”
Section: ■ Introductionsupporting
confidence: 79%
See 3 more Smart Citations